Is there something special about palmitoleate? - Hodson, L; Karpe, F (2013)
Purpose of Review: The fatty acid, palmitoleate (16:1 n-7), has received a lot of attention in recent years for being 'lipokine' and for the first time, we review the evidence to determine if there is something special about palmitoleate in humans. Recent Findings: Despite dietary intakes being low (<4% of total energy) palmitoleate is the second most abundant monounsaturated fatty acid in most, but not all, blood lipid pools and notably more abundant in adipose tissue. Thus, compared with other fatty acids, the palmitoleate content of lipid pools must be influenced by endogenous synthesis, which appears to be tissue and depot specific. We present a summary of dietary intervention studies of food components enriched in palmitoleate but this gives inconclusive results in regards to an impact on human metabolic regulation. Summary: To date, there is no strong evidence from human studies suggesting that palmitoleate has 'lipokine' effects. However, unlike other fatty acids, there is a clear tendency towards compartmentalization and tissue-specific formation of palmitoleate, which is intriguing and requires further investigation. © 2013 Wolters Kluwer Health | Lippincott Williams and Wilkins.